Currency Valuation : A Medium-Term Horizon View - Havuluoto, Arttu (My University, 2023)
This thesis studies the medium-term horizon predictability of nominal exchange rate changes using a currency value signal. The currency value is derived from different purchasing power parity indica-tors. The goal of the thesis is to extend the prevailing currency value signal’s short-term predictive content of excess currency returns, to medium-term horizon nominal exchange rate changes context. Previous studies have examined the short-term predictability power of currency value over future excess currency returns. The literature has found that currency value strategies can generate abnor-mal returns on a short-term horizon, from one month to one quarter. Recently, studies about cur-rency value have been employing purchasing power parity indicators to account for the currency value. To be precise, the five-year change in RER has emerged as a generally used indicator of curren-cy value in the literature. The study contributes to the existing literature by answering the main re-search question of whether it is possible to predict future medium-term nominal exchange rate changes using currency value signals. In addition, the study accounts for the cross-sectional differ-ences in the selected macro fundamentals to get a clearer measure of currency value which is not dependable on fundamentals of the economies. The thesis starts the examination with regression analysis and further moves on to strengthen the results using portfolio sorts. Therefore, the regression analysis is used to find a positive relationship between the currency value indicator and subsequent nominal exchange rate changes. Then, the macro fundamentals are included to see if the predictability increases. After that, predictability is evaluated for different currency groups. Next, the portfolio sorts start from the short-term assess-ment to see if the results here are in line with the previous studies. Continuing to the hitherto unex-plored area, the overlapping holding period portfolios are used to evaluate the medium-term hori-zon predictability. Lastly, the additional results provide a wide range view of the real exchange rate dynamics and the current state of the studied signal. The results show that by accounting for the macro fundamentals, it is possible to enhance the cur-rency value signal’s predictable power for both short-term and medium-term horizons. Hence, the expected inflation differentials emerge as the most influential macro factor to account for when predicting the nominal exchange rate changes. In addition, the study finds that safe haven and emerging market currency groups have dissimilar expected future changes in the nominal exchange rates compared to the base group. Further on, the overlapping holding period portfolio sorts show that the unadjusted currency value signal is unable to beat a random walk, characterized by an equal weight market portfolio of sample currencies. Nonetheless, when adjusting the currency value signal, the performance increases significantly compared to the unadjusted signal. The additional results find that currently, the five-year change in RER power to predict the subsequent nominal exchange rate changes is poor.

Tämä tutkimus tutkii nimellisten valuuttakurssimuutosten keskipitkän aikavälin ennustettavuutta valuutta arvosignaalin avulla. Valuutan arvo mittari on johdettu eri ostovoimapariteetti indikaattoreista. Tutkimuksen tavoitteena on laajentaa vallitsevan valuutta arvosignaalin lyhyen aikavälin ennustesisältöä koskemaan keskipitkän aikavälin valuuttakurssimuutoksia. Aiemmat tutkimukset ovat tutkineet valuutan arvofaktorin lyhyen aikavälin ennustamiskykyä koko-naisvaluuttatuoton ennustajana. Kirjallisuudessa on havaittu, että valuutta-arvostrategiat voivat tuottaa epänormaaleja tuottoja lyhyellä aikavälillä, kuukaudesta yhteen kvartaaliin. Viime aikoina valuutta-arvoa koskevissa tutkimuksissa on käytetty ostovoimapariteetti indikaattoreita valuutan arvon indikaattorina. Tarkemmin sanottuna viiden vuoden muutos reaalisessa valuuttakurssissa on noussut yleisesti käytetyksi valuutan arvon indikaattoriksi kirjallisuudessa. Tutkimus täydentää ole-massa olevaa kirjallisuutta vastaamalla pääasialliseen tutkimuskysymykseen, onko mahdollista ennustaa tulevaisuuden keskipitkän aikavälin valuuttakurssimuutoksia valuutta-arvo signaaleilla. Lisäksi tutkimuksessa huomioidaan valittujen makrofundamenttien poikkileikkauserot, jotta valuutta-arvosta saadaan selkeämpi mitta, joka ei ole riippuvainen talouksien perustekijöistä. Tutkimus aloittaa tarkastelun regressioanalyysillä ja jatkaa tulosten vahvistamiseen portfoliolajitteluilla. Regressioanalyysiä käytetään löytämään positiivinen suhde valuutan arvon indikaattorin ja sitä seuraavien nimellisten valuuttakurssimuutosten välillä. Sitten makrofundamentit otetaan mukaan tarkasteluun, ja tutkitaan, paraneeko ennustettavuus. Tämän jälkeen ennustettavuutta arvioidaan eri valuuttaryhmille. Seuraavaksi portfoliolajittelut alkavat ensin lyhyen aikavälin ennustettavuuden arvioinnista, jotta nähdään, ovatko tulokset linjassa aikaisempien tutkimusten kanssa. Sen jälkeen jatketaan toistaiseksi tutkimattomalle alueelle, päällekkäisten omistusjaksojen portfolioiden avulla arvioidaan keskipitkän aikavälin ennustettavuutta. Lopuksi lisätulokset tarjoavat laajan katsauksen reaalisen valuuttakurssin dynamiikasta ja tutkitun signaalin nykytilasta. Tulokset osoittavat, että ottamalla huomioon makronfundamentit, on mahdollista parantaa valuutta-arvosignaalin ennustavaa tehoa sekä lyhyellä että keskipitkällä aikavälillä. Odotetut inflaatioerot nousevat vaikuttavimmaksi makrotekijäksi, joka on tarpeellista ottaa huomioon ennustettaessa nimellisten valuuttakurssien muutoksia. Lisäksi tutkimuksessa havaitaan, että turvasatama- ja kehittyvien markkinoiden valuuttaryhmillä on erilaiset tuotto-odotukset nimellisvaluuttakursseissa perus-ryhmään verrattuna. Päällekkäiset omistusjakson portfoliot osoittavat, että ei-mukautettu valuutta-arvosignaali ei pysty päihittämään markkinaportfoliota, joka on koostettu otantaan kuuluvista valuu-toista yhtäläisillä painoilla. Siitä huolimatta valuutta-arvosignaalia mukautettaessa makrofundamenteilla suorituskyky paranee merkittävästi ei-mukautettuun signaaliin verrattuna. Lisätulokset osoittavat, että tällä hetkellä viiden vuoden muutos reaalisessa valuuttakurssissa on heikko estimaattori tulevien nimellisten valuuttakurssimuutosten ennustamisessa niin lyhyellä kuin keskipitkällä aikavälillä.
Keywords: rates of exchange; currency; foreign exchange market; forecasts; purchasing power; portfolios; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance